ANALISIS INOVASI ADMINISTRASI GURU DALAM MENINGKATKAN MUTU PEMBELAJARAN (STUDI MAN REJANG LEBONG) - Idi Warsah; Nuzuar Nuzuar (Badan Litbang dan Diklat Kementerian Agama RI, 2018)
AbstractThis research was a descriptive research, conducted by using a quantitative approach. The research aimed to study the administrative innovation carried out by the teachers in MAN (Islamic Senior High School) Rejang Lebong and the obstacles faced by the teachers in conducting the innovation. Data was obtained by delivering questionnaires to 54 teachers in MAN Rejang Lebong. Questionnaires consisted of two parts, i.e.: 1) data regarding teacher’s innovation and 2) data regarding teacher’s obstacles in conducting the administrative innovation. Data was processed by using a percentage and a likert scale to determine the interval. The findings in this research explained that the teachers in MAN Rejang Lebong have conducted the administrative innovation. However, the innovation conducted has not been optimally done, i.e. 61,5%, with a 62,15% innovation on prota (annual program); a 61,67% innovation on promes (semester program); a 58,72% innovation on syllabus; a 63,75% innovation on RPP (Lesson Plan). The obstacles that are interrupting the teachers in conducting the innovation, i.e. i) time constraint due to the teacher’s tight performance schedule, ii) ever-changing curriculum, iii) the lack of carrying capacity, facilities, and infrastructure, iv) leadership, and v) technical guidance and administrative management.Abstrak Penelitian ini adalah penelitian deskriptif dengan pendekatan kuantitatif yang bertujuan untuk mengetahui inovasi administrasi yang dilakukan guru di MAN Rejang Lebong, dan hambatan-hambatan apa saja yang dihadapi guru dalam melakukan inovasi administrasi tersebut. Data diperoleh dengan cara menyebarkan angket kepada 54 guru MAN Rejang Lebong. Angket terdiri dari dua yakni untuk mendapatkan data mengenai inovasi guru dan data mengenai hambatan guru dalam melakukan inovasi administrasi. Data diolah dengan persentase dan rumus skala likert untuk menentukan intervalnya. Temuan penelitian ini menunjukkan guru-guru MAN Rejang Lebong telah melakukan inovasi administrasi, akan tetapi inovasi yang dilakukakan belum maksimal, yaitu sebesar 61,57%, dengan 62,15% inovasi pada Prota, 61,67% inovasi pada promes, 58,72% inovasi pada silabus, dan 63,75% inovasi pada RPP. Adapun faktor-faktor yang menghambat guru-guru tersebut dalam berinovasi yaitu keterbatasan waktu karena padatnya jadwal kinerja guru, kurikulum yang sering berubah, kurangnya daya dukung, sarana, dan prasarana, masalah kepemimpinan, dan kurangnya bimtek dan pengelolaan administrasi.